¿Propiedad sin ley?: por qué las leyes de titulación y la prescripción adquisitiva no resuelven el problema de la «propiedad informal» - Guillermo Arribas (Revista Iberoamericana de Estudios de Desarrollo)
It is common to find «informal ownership» in Latin America in the context of illegal takings. Human settlements in Peru, favelas in Brazil, or camps in Chile, in all cases, a group of people builds land rights outside the law. Although this phenomenon has been analyzed many times from an economic perspective, mostly proposing the granting of property titles as a solution, the review of the Peruvian case shows its ineffectiveness. In 1982, 53.54 % of the houses in Peru had property titles; however, after almost forty years and multiple land titling laws, in 2017 this percentage dropped to 50.65 %. Moreover, between 2001 and 2018, 46 % of new housing was built upon informal property through illegal takings. The present investigation proposes another view from the legal perspective, investigating on the traditional civil institution of the adverse possession, and offering a refocus to the problem.